Football Spending for Success: Analyzing Investment and Team Performance in NCAA FBS Programs - Keunsu Han; Jin Dong Park; Kyungeun (Karry) Kwon (Journal of Applied Sports Management, 2025)
This study examines the relationship between financial investment and team performance in NCAA Division I Football Bowl Subdivision (FBS) football programs from 2010 to 2023. Key variables include total football spending, head coach salaries and bonuses, and win-loss records. Ordinary Least Squares (OLS) regression models were used to examine these associations, controlling for conference affiliation by distinguishing between the so-called power and non-power conferences. The results indicate that greater investment in football operations and coaching compensation is significantly associated with higher win percentages, particularly within power conference programs. However, the impact of financial investment on final rankings differs by conference type. Total football spending is a significant predictor of rankings in power conferences, whereas head coach salary is the only significant predictor in non-power conferences. These findings suggest that financial investment enhances team performance, though its effectiveness varies depending on institutional context.
Keywords: NCAA FBS Programs; Football Spending; Head Coach Compensation; Team Performance